2022
DOI: 10.3389/fcvm.2022.899327
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasonography Enables the Detection of a Cold Pressor Test-Induced Increase in Renal Microcirculation in Healthy Participants

Abstract: BackgroundRenal microcirculation is essential for regulation of the glomerular filtration rate, the reabsorption of salt and water from the interstitium, and hence the blood pressure. Renal ultrasonography coupled to Doppler analysis and contrast-enhanced ultrasound enables the study of renal perfusion. So far, physiologic interventions have rarely been performed to assess the renal perfusion. The objective of our study was to measure the renal perfusion in response to a cold pressor test (CPT).MethodsHealthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Limitations of our study include the unexpected large inter-individual differences in PI (SD > 50% than initially estimated), which makes our study underpowered to fully assess the determinants influencing the PI. Whether this can be explained by differences in systemic and intra-renal RAAS activity, unknown other clinical variables such as the degree of expression of AT1 and AT2 receptors, the integrity of the endothelium or renal sympathetic system activation is still an open question and should be accounted for in future studies [ 14 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of our study include the unexpected large inter-individual differences in PI (SD > 50% than initially estimated), which makes our study underpowered to fully assess the determinants influencing the PI. Whether this can be explained by differences in systemic and intra-renal RAAS activity, unknown other clinical variables such as the degree of expression of AT1 and AT2 receptors, the integrity of the endothelium or renal sympathetic system activation is still an open question and should be accounted for in future studies [ 14 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the healthy volunteers participated to both studies. Details of the two studies have been described previously [12,14]. In brief, the inclusion criteria for all the healthy controls in both studies were: age ≥ 18 years, being normotensive (office blood pressure < 135/85 mmHg) and not taking any medications.…”
Section: Study Populationmentioning
confidence: 99%
“…A modified CPT was applied as previously described [ 7 ]. Both feet were placed in a footbath filled with water at body temperature (35–37°C, sham) for baseline measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Renal ultrasound was performed on a Samsung RS80A device using a dedicated abdominal probe (3–5 MHz) as described previously [ 7 ]. The RRI was measured in a segmental artery with the easiest accessibility and highest quality of waveforms, and in expiratory breath-hold.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, sympathetic nervous system activity on the external carotid artery (ECA), internal carotid artery (ICA), and middle cerebral artery (MCA) was investigated, and it was shown that the carotid arteries respond to painful stimuli with vasodilation [ 22 ]. On the other hand, a contrast-enhanced Doppler study demonstrated that CPT increases renal microcirculation in healthy individuals [ 23 ]. Studies have also shown that CPT causes coronary vasodilation in healthy individuals [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%